Parading respectability: the Christmas Bands Movement in the Western Cape, South Africa and the constitution of subjectivity. - Bruinders, Sylvia (International Library of African Music, 2010)
In my research on the Christmas Bands Movement in the Western Cape (November 2003 to March 2006), which this extract from my field notes speaks to, I have often observed how important it is for the bands to display their respectability and discipline. In this article I investigate how the bands constitute themselves as respectable members of society through disciplinary routines, uniform dress, and military gestures.
Keywords: South Africa; African Music